1967
DOI: 10.1149/1.2426594
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of the Chemical Polishing of a-Corundum Surfaces with Vanadium Pentoxide

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1967
1967
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…However, after treatment with one of the etchants (none of which dissolve sapphire at an appreciable rate at etching temperatures), the surface showed a highly scratched appearance. This effect has been noted by others (6). Hockey (10) has shown that after fine polishing, the surface is highly distorted and has a high dislocation density.…”
Section: Experimental Methodssupporting
confidence: 60%
See 3 more Smart Citations
“…However, after treatment with one of the etchants (none of which dissolve sapphire at an appreciable rate at etching temperatures), the surface showed a highly scratched appearance. This effect has been noted by others (6). Hockey (10) has shown that after fine polishing, the surface is highly distorted and has a high dislocation density.…”
Section: Experimental Methodssupporting
confidence: 60%
“…The structure and the effect of electrolytic breakdown of anodic oxide films on silicon were considered by some authors (5,6). Schmidt and Owen (5) found that anodic films grown on silicon in phosphoric acid were of three types: completely structureless nonporous films, films with round spots of increased film thickness and films with round holes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Depositions have also been performed on substrates cut from Czochralski boules, some of which have been mechanically polished only and other subsequently chemically polished in vanadium pentoxide, using the process developed by Faktor et al (1967). Silicon films have also been deposited on vapour grown (0001) plane platelets about 5 pm thick which were completely free from mechanical damage and were also virtually free from crystallographic imperfections except for a few growth steps.…”
Section: Substratesmentioning
confidence: 99%